Routine pathologic evaluation of circular stapler anastomotic rings is not useful after resection for colorectal cancer: retrospective study and systematic review with meta-analysis. Issue 5 (12th October 2022) - Holden, James R; McIntosh, Pam; Johnson, Garrett G R J; Park, Jason; Hochman, David J; Vergis, Ashley; Yip, Benson; Helewa, Ramzi M; Hyun, Eric
Abstract: Background: Circular staplers are commonly used for reconstruction after radical resection for colorectal cancer. Pathological analysis of the anastomotic rings is common practice, although the benefits are unclear. The purpose of this study was to evaluate the usefulness of routine histopathological analysis of anastomotic rings in an original series and in a systematic review of the literature. Method: The retrospective study was performed at two university-associated academic hospitals in Winnipeg, Canada, including patients investigated for colorectal cancers (within 30 cm of the anal verge) who underwent resection between 2007 and 2020. The systematic review involved Ovid MEDLINE, Embase, Scopus, and Web of Science databases, selecting for adult human studies involving analysis of anastomotic rings in elective colorectal cancer resections. The main outcome measure was the proportion of patients with cancer in the anastomotic ring specimens. The frequency of benign pathology findings and changes to patient management were also examined. Results: Out of 673 eligible patients, 487 were included in the retrospective analysis. No patients had cancer within the anastomotic ring specimens. Twenty-five patients (5.1 per cent) had benign pathological findings within the anastomotic ring specimens, and patient management was never affected. In the systematic review, 27 articles were included in the final analysis out of 5848 records reviewed. The rate of cancer within anastomotic ring specimens was 0.34 per cent, and the rate of change in patient management was 0.19 per cent. Conclusion: The likelihood of finding cancer within anastomotic rings is rare and their histopathological examination seldom changes patient management. Abstract : This study was designed to evaluate the usefulness of sending circular stapler anastomotic rings for histopathological analysis. It included a retrospective study of 487 patients and a systematic review of the literature. Our results indicate that finding cancer within the anastomotic ring specimens is rare, and alterations to patient management because of these results is even rarer.